Quality & safety aspects of nuclear medicine practice: Definitions and review of the current literature - Giannoula, Evanthia I.; Panagiotidis, Emmanouil; Katsikavelas, Ioannis; Chatzipavlidou, Vasiliki D.; Sachpekidis, Christos; Bamidis, Panagiotis D.; Raftopoulos, Vasilios; Iakovou, Ioannis P. (My University, 2020)
Current literature records a glaring discrepancy between the rapid developments and progress of medicine and the simultaneous deterioration of the quality and safety of the provided health care services. Bibliographic data as far as perceptions of quality and safety in nuclear medicine departments are concerned, are limited and frequently ambiguous. Most nuclear medicine departments provide the same types of services, but not the same quality of service, while patients' perceptions are not always matched by the perceptions of health care providers. The multidimensional nature of quality and safety, deriving from the different criteria and standards by which different groups of the population attempt to interpret and evaluate them, justifies these discrepancies, over most of quality's and safety's dimensions studied. Nuclear medicine's unique characteristic of using radiopharmaceuticals, exposing to ionizing radiation affects dramatically these perceptions, irrespective of whether quality and safety assurance measures already cover radiation protection, instrumentation maintenance, radiopharmaceutical handling, and the management of all the other aspects of patient care. On the other end of the spectrum, patient-centred practice, communication and proper information play as a well decisive role in ensuring patients' satisfaction.
Keywords: Quality-of-Care; Patient Safety; Safety of Staff; Communication; Doctor-Patient Relationship; Health Care